CSR disclosure and financial access: a case study of Pakistan - Anwar, Zeshan; Abbas, Kausar; Khan, Madiha; Abdul Razak, Dzuljastri (Kulliyyah of Economics, International Islamic University Malaysia, 2019)
This study aimed at examining the association of Corporate Social Responsibility (CSR) disclosure with access to finance by estimating the level of financial constraints faced by listed firms of the Pakistan Stock Exchange. CSR disclosure (CSRD) is attracting the attention of researchers and stakeholders and also becoming a vital source of competitiveness and information dissemination. Many businesses in Pakistan have developed the structure for CSR activities but the awareness of CSR concept and its disclosure is still limited in Pakistan. Panel data set has been used from annual reports of 55 non-financial companies listed on the Pakistan Stock Exchange during the period 2013 to 2017 to investigate the impact of CSRD on financial access of firms by estimating the level of capital constraints they faced. The results reveal a significant positive impact of CSRD on firm financial access; the firms with higher CSRD face fewer capital constraints, resulting in better financial access. This study contributes to existing CSR literature which highlights the vital role that capital markets play in assessing the potential for long-run value creation by firms adopting CSR strategies. This study further highlights the relationship between capital markets and socially responsible firms by focusing on the critical impact of CSRD on the firm’s capital constraints. It contributes to an emerging literature inside CSRD which highlights the vital role played by capital markets in assessing the potential for long-run value creation by firms adopting CSR strategies. This study further highlights the relationship between capital markets and socially responsible firms by focusing on the critical impact of CSRD on the firm’s capital constraints. It provides a better understanding of legitimacy and stakeholder theory which motivates firms for CSRD and also makes a significant methodological contribution to CSRD literature by developing the CSRD index.